2021
DOI: 10.1186/s12938-021-00882-8
|View full text |Cite
|
Sign up to set email alerts
|

Event-related EEG oscillatory responses elicited by dynamic facial expression

Abstract: Background Recognition of facial expressions (FEs) plays a crucial role in social interactions. Most studies on FE recognition use static (image) stimuli, even though real-life FEs are dynamic. FE processing is complex and multifaceted, and its neural correlates remain unclear. Transitioning from static to dynamic FE stimuli might help disentangle the neural oscillatory mechanisms underlying face processing and recognition of emotion expression. To our knowledge, we here present the first time–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…They indicate a greater reactivity of the high-frequency part of the EEG spectral parameters, especially in response to the negative modality of demonstrated faces. Apart from that, emphasis was placed on the high significance of the theta EEG oscillations in the anterior cortical areas alongside high-frequency bands in the temporal, parietal and occipital regions (presumably including the fusiform gyrus), which play a crucial role in the mechanisms of facial perception and processing [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…They indicate a greater reactivity of the high-frequency part of the EEG spectral parameters, especially in response to the negative modality of demonstrated faces. Apart from that, emphasis was placed on the high significance of the theta EEG oscillations in the anterior cortical areas alongside high-frequency bands in the temporal, parietal and occipital regions (presumably including the fusiform gyrus), which play a crucial role in the mechanisms of facial perception and processing [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In the change detection of an emotion task, it was found that all modes of emotion changes resulted in enhanced theta synchronization, which correlates with the performance accuracy of subjects during emotion change detection, but the same cannot be concluded for alpha or beta bands [101]. Another study by Aktürk and team showed increased power and higher phase-locking values for theta (as well as all other frequencies) in the right parietal region when a face was first perceived and that this increase in power is greater for emotional expressions than neutral ones [132]. In addition, they found that theta phase-locking values were higher for fearful than happy or neutral expressions.…”
Section: Theta Bandmentioning
confidence: 93%